The effect of using the cognitive modeling strategy in learning drawing skills among middle school female students (Journal of the College of Basic Education, 2024)
The current research aims to identify the effect of using the cognitive modeling strategy in learning drawing skills among middle school female students. For the purpose of verifying the research objective, two null hypotheses were formulated and subjected to experimentation. The research was also limited to middle school female students in Al-Karkh, the first of the 2023 semester, and the researcher used The experimental approach, as the research sample consisted of (63) female students distributed into two groups, the first was experimental and studied according to the cognitive modeling strategy and the other was control, studied according to the usual method. The researcher used the following statistical methods to address the results:(T-test for two independent groups, variance, standard deviation, chi-square, difficulty and discrimination coefficient, effectiveness of false alternatives, Pearson correlation, and Spearman-Brown corrective equation) The experiment began on Sunday (10/15/2023). The researcher concluded that adopting the cognitive modeling strategy had Positive effect in raising the level of drawing skills among female students.